Editorial: The Rationale for Multi-drug Therapy (The East and Central African Journal of Pharmaceutical Sciences, 2020)
In literature, the terms Multidrug Therapy (MDT) and Combination Therapy (CT) are usedinterchangeably and refer to concurrent use of 2 or more drugs in the management of diseases. Inchemotherapy of cancer, malaria, HIV/AIDs, tuberculosis and leprosy Multiple Drug Therapy is therule rather than exception. MDT is used to exploit synergistic and additive potential of individualdrugs without increasing the toxicity of the combination. A tacit understanding is that such drugs willhave different biochemical targets (different mechanism of action) and their toxicity will not beadditive or complementary.